2020
DOI: 10.3390/ani10061066
|View full text |Cite
|
Sign up to set email alerts
|

Blood L-Lactate Concentration as an Indicator of Outcome in Roe Deer (Capreolus capreolus) Admitted to a Wildlife Rescue Center

Abstract: Roe deer (Capreolus capreolus) are among the most frequent patients of rescue centers in Italy. Three outcomes are possible: natural death, euthanasia, or treatment and release. The aim of the present study is to propose blood L-lactate concentration as a possible prognostic biomarker that may assist veterinarians in the decision-making process. Sixty-three roe deer, admitted to one rescue center in the period between July 2018 and July 2019, were sampled and divided into 4 groups according to their outcome: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Our results showed that the main reasons for rescue and hospitalization were traumatic injuries and the most represented was trauma caused by certain or assumed collisions with vehicles. A study about rescued roe deer carried out in Emilia-Romagna (Italy) showed similar findings, with a prevalence of 71.4% of patients hospitalized for trauma [ 24 ]. Our results are in line also with previous reports [ 3 , 4 ] in which the prevalence for rescue was evaluated in a more limited geographical area in Tuscany (municipality of Pisa).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our results showed that the main reasons for rescue and hospitalization were traumatic injuries and the most represented was trauma caused by certain or assumed collisions with vehicles. A study about rescued roe deer carried out in Emilia-Romagna (Italy) showed similar findings, with a prevalence of 71.4% of patients hospitalized for trauma [ 24 ]. Our results are in line also with previous reports [ 3 , 4 ] in which the prevalence for rescue was evaluated in a more limited geographical area in Tuscany (municipality of Pisa).…”
Section: Discussionmentioning
confidence: 62%
“…Several authors have underlined that animal–vehicle collisions are usually unreported, and that accurate records are lacking [ 24 , 30 , 31 , 32 ], leading to an incorrect evaluation and monitoring of the current situation. Moreover, different ecological factors, such as density, areas with different landscapes, climates, and population structures influence the probability of deer having a car accident [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…While limited, there are studies that have used lactate as a measure of welfare in other animals, including pigs raised for meat production [29,30], deer in a wildlife rescue center [31], and the effect of capture in wild tortoises, turtles, and snakes [18,32,33]. One study on zoo-housed American flamingoes (Phoenicopterus ruber) used lactate to evaluate the effects of capture time and difficulty, finding that lactate levels significantly increased with time of capture but not with difficulty of capture [34].…”
Section: Introductionmentioning
confidence: 99%
“…There are few papers regarding the reference ranges for the haematological and biochemical parameters of roe deer [ 19 , 28 , 29 , 30 , 31 ]. The aim of this study was thus to evaluate the haematological and biochemical parameters in traumatised roe and to discuss their values in relation to the animals’ hospitalisation outcomes.…”
Section: Introductionmentioning
confidence: 99%